Aby Warburg in Joan Jonas's Natural World - Bonilla Elizondo, Pablo (2022)
This paper analyzes the links between the work of Joan Jonas and the thought of Aby Warburg, which can be clearly identified in one of her latest performances: The Shape, the scents, the feel of things (2006), where Warburg appears as the protagonist. However, this article also reviews Jonas previous work to find in it a series of coherent signifiers, motifs and processes that makes possible to understand the background of an appropriation process that places Warburg’s thought in the symbolic space traced by Jonas, between body and territory.